WATER PRESSURE EQUALIZATION IN PIPE NETWORK CASE STUDY: AL-KARADA AREAS IN BAGHDAD - Rafa Hashim Al-Suhaily; Awatif Soaded Abdul-Hameed; Hameed Mirza Mita´b (Journal of Engineering, 2006)
In order to make a balance between the increasing of potable water demand and the available quantity, a pipe network should be managed in an optimal hydraulic operation state. The optimal operation of a water supply network leads to minimize the effect of the variance in pressure between the available and minimum required pressure head. It simulates the hydraulic model and puts the optimized project with the constraints (minimum design head=20 m, and the available commercial pipe diameter, 1600³D³250 mm). The objective function is to minimize the cost for the suggested hydraulic solution to a minimum value. Pressure uniformity coefficient (UC), Standard deviation () and coefficient of variance (Cv) are used to show that the pressure head at the nodes of the network is uniformly distributed. The optimal design of the case study (R9 water supply network) has an actual cost of 561,169,310 ID and the uniformity indices of UC=99.565, =3.6508 and Cv=0.1543 while the existing design has cost of 856,617,170 ID with the uniformity indices of UC=97.909, =3.5977 and Cv=0.7906. Hence there is a benefit of 34.5% in the cost of the optimal design used in this study, with high uniformity coefficient. The effect of Hazen-William coefficient (C) on total cost showed an inversely linear effect. For the value of C=130, the actual cost was 600,898,300 ID, i.e., the penalty cost approached to zero and has no effect on the total cost.